2003
DOI: 10.1017/s0952836903003820
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism of body size and shell shape in European tortoises

Abstract: Adult body size and shape were examined in almost 1400 individuals of the tortoises Testudo graeca, T. hermanni and T. marginata from Greece. The size at maturity was greater in females than in males in all three species. Maximum and mean adult sizes were also greater in females than in males in T. graeca and T. hermanni. Males grew to a larger size than females in T. marginata, and mean adult size was similar in the sexes in this species. Sexual dimorphism of shape (adjusted for size covariate) was shown in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
110
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(120 citation statements)
references
References 39 publications
10
110
0
Order By: Relevance
“…The large marginal bottom plate of males is often curved down. The shell form of females is simpler: the lower part of the carapace is narrower than the middle of the shell and the marginal plate almost touches the ground [10]. Changes in the shape and construction of the shell are noticed, and do not appear equally in both genders.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The large marginal bottom plate of males is often curved down. The shell form of females is simpler: the lower part of the carapace is narrower than the middle of the shell and the marginal plate almost touches the ground [10]. Changes in the shape and construction of the shell are noticed, and do not appear equally in both genders.…”
Section: Resultsmentioning
confidence: 94%
“…Gender was determined on the basis of external characteristics. They were distinguished by external shape of the skeleton, the shape of the rear lateral scute, width at anal and supracaudal level, shape and size of the tail [3,10,11]. Adult animals are considered as 13 cm in size for males and over 15 cm for females [10].…”
Section: Methodsmentioning
confidence: 99%
“…Many causal explanations have been suggested for the differences in shell shape between males and females. For example, it has been suggested that females need to develop more voluminous (and hence more spherical) shells using a given amount of shell material to increase clutch size (Brophy, 2006;Tucker et al, 1998;Willemsen and Hailey, 2003). Similarly, the flatter shells and larger limb apertures of males have been explained as adaptations to facilitate locomotion for dispersal or mate searching, and the concave plastra of terrestrial males have been suggested to increase stability during mating (Pritchard, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Both righting behaviour (Ashe 1970;Wassersug & Izumi-Kurotani 1993;Rivera et al 2004;Stancher et al 2006) and the evolution of shell morphology (Rouault & Blanc 1978;Claude et al 2003;Myers et al 2006) of turtles have been studied recently. An example of their interaction is the sexual dimorphism of species where males are often overturned during combats (Bonnet et al 2001;Willemsen & Hailey 2003;Mann et al 2006), and their shell has adapted to facilitate righting. Here we develop a geometric shell model based on field data to uncover systematically the connections between righting strategies and turtle shell morphology.…”
Section: Introductionmentioning
confidence: 99%